Academic Supervision Based on Coaching Clinic to Improve Teachers Pedagogic Competence - Susilowaty Susilowaty; Ade Tutty Rokhayati Rosa (Journal of Science and Education (JSE), 2026)
This study aims to analyze the implementation of academic supervision based on a coaching clinic approach in improving elementary school teachers’ pedagogical competence. A qualitative case study design was employed at SD Negeri Kalideres 04 Petang (Afternoon Public Elementary School) and SDS Muslimat Kalideres (Muslimat Kalideres Private Elementary School) in West Jakarta. Participants included principals, teachers, and school supervisors selected through purposive sampling. Data were collected through in-depth interviews, participatory observations, and document analysis, and analyzed using Miles, Huberman, and Saldana’s interactive model. The findings reveal that applying the POAC management functions (Planning, Organizing, Actuating, Controlling) within academic supervision enhanced teachers’ reflection, strengthened lesson planning, and encouraged more innovative and contextual teaching practices. Academic supervision was no longer perceived as one-sided control but as a collaborative and professional mentoring process. This study is expected to provide practical contributions to developing a participatory supervision culture and enrich educational management literature on sustainable teacher development, thereby improving the overall quality of elementary education in the future.